The Process of Strengthening Reading Interest in Students Through School Literacy Movement Activities - Destian Ariyanto; M. Hosnan; Ujang Jamaludin (Universitas Pendidikan Ganesha, 2020)
Reading interest in Indonesian students is still relatively low based on data from the Central Bureau of Statistics (BPS). In 2018 reading levels ranging from reading newspapers, in the countryside shows 7.43 and in urban 22.68 and rural and urban areas 15.06. Reading textbooks in rural areas also showed a figure of 19.03 and in urban 21.95 and rural and urban 20.49. This study explores the planning, implementation, and evaluation and supporting and inhibitory factors in strengthening reading interest through the School Literacy Movement's activities. This research uses a qualitative descriptive research method which is a research method that aims to describe phenomena that occur objectively. The results show that this School Literacy Movement activity provides excellent benefits for the school and students. It started from the increased interest in reading and many characters' education values such as discipline, and responsibility gained from the activity.